Upaya Peningkatan Kemampuan Peserta Didik dalam Memahami Cerita Pendek Melalui Kombinasi Model Pembelajaran Jigsaw dan STAD di SMP Negeri 1 Kedungreja Cilacap - Siti Mariyam (Universitas Pendidikan Mandalika, 2022)
The purpose of this study was to improve the ability of students to examine the structure and linguistic aspects of short stories using a contextual approach to a combination of Jigsaw and STAD learning models. This research method uses classroom action research. The research subjects were 32 students of class IXF SMPN 1 Kedungreja. The data collection technique of this research used observation sheets and tests. While the data analysis technique is descriptive analysis. The results of this study indicate that the application of a contextual approach to the combination of Jigsaw and STAD learning models can improve students' abilities in studying the structure and linguistic aspects of short stories. The results achieved in Cycle I, the class average score in succession, the final score was 76, the expert group score was 75, the origin group score was 76, and the quiz score was 78. While in Cycle II the class average score was 90, the group score was 93 experts, 87 original group scores, and 89 quiz scores, and all students experienced complete learning.